Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Patterns and mechanisms of cross-media antimicrobial resistance development in a typical reclaimed water-receiving urban river - Bang-Ze Li; Shu-Hao Du; Han-Lin Cui; Xin-Xin Gao; Jia-Hao Wu; Bei-Ying Li; Shu-Hong Gao; Ai-Jie Wang; Bin Liang (Water Research, 2026)

The unintentional adverse effect of Fe3 + on trimethoprim adsorption at environmentally relevant concentration by extracellular polymeric substances - You Ma; Tian-Yu Li; Zi-Yi Fan; Han Meng; Guo-Xiang Wang; Fang Fang; Yu-Dong Chen; Run-Ze Xu; Wen-Ming Xie (Journal of Environmental Chemical Engineering, 2026)

Metal-polyphenol network-coated probiotic microcapsules: Enhancing Limosilactobacillus fermentum storage stability and yogurt characteristics - Yi-han Cai; Fang Huang; Si-ying Yan; Xiao-jin Lin; Shu-ling Huang; Shao-fu Feng; Jie-ying Chen; Yan-yan Huang; Xin-An Zeng; Xiang-ze Jia (International Dairy Journal, 2026)

Naturally occurring biopterin as a photosensitizer for enhanced photodegradation of sulfonamides in aquatic environments - Bing Li; Yu-Ze Han; Ye-Chao Tian; Xin Wang; Chi-Cheng Deng; Xiao-Ya Zhou; Shuo Zhang; Yan-Ting Zuo; Wen-Tao Li; Ai-Min Li (Environmental Pollution, 2026)

Morphological engineering and valence state strategy enable stable nitrate-to-ammonia electroconversion at copper surface in the wide pH range - Yue-Han Qin; Xiao-Hui Wang; Ze-Nong Zhang; Shi-Bin Yin; Cong-Cong Han; Xuan Ai; Shu-Ni Li; Xin Wang; Yu Chen (Chemical Engineering Journal, 2026)

Rosa roxburghii-derived Mg-doped carbon dots as bioactive nanoregulators in hydrogel scaffolds: orchestrating Nrf2/NF-κB signaling for enhanced periodontal repair in diabetes - Xuedong Deng; Lingxiang Sun; Xi Chen; Zheng Wang; Yilin Ping; Wen Ze Han; Lu Wang; Tingting Wu; Yifan Zhao; Bing Li; Xiuping Wu (Chemical Engineering Journal, 2026)

Prediction of bending buckling in subsea lined pipes using FEM-based machine learning with equivalent geometric imperfection factor - Tianping Gu; Yuhang Han; Jianbing Zhang; Xin Wang; Ze Wu; Guangyuan Weng (Ocean Engineering, 2026)

Experimental and numerical investigation into the interfacial performance of Fe-SMA strips bonded to cold-formed steel C-section substrates - Hai-Tao Wang; Wen Su; Han-Ying Qi; Zhiqiang Dong; Xinliang Sun; Run-Ze Zhu (Engineering Structures, 2026)

Impacts of international and interprovincial trade on red list species of vertebrate in China - Changbo Wang; Wendie Wang; Xilong Yan; Mingyue Pang; Lixiao Zhang; Ze Wang; Jinliang Liu; Jing Han; Meili Feng (Ecological Economics, 2026)

GNPS-guided discovery of antifungal brominated metabolites from Chaetomium elatum FH-3 via NaBr-regulation and biotransformation - Jing-jing Su; Yin-han Teng; Bai-xue Yin; Hai-fang Wang; Yu-ze Li; Wei Wang; Xiao-mei Song; Dong-dong Zhang; Hao Fan (Phytochemistry Letters, 2026)

Petrology and geochemistry of monzogranite and porphyritic granite in Laowan ore field of Qinling orogenic belt, China: Implications for gold and molybdenum mineralization - Ying-nan Chen; Cheng Xu; Wen-lei Song; Wei Fu; Ze-bang Yi; Zhi-xuan Han; Chengyu Zou; Jian-li Chen (Journal of Asian Earth Sciences, 2026)

Effects of mesoscale eddies on near-bottom dynamics in the continental slope of northern South China Sea - Hao Chen; Shuang-Xi Guo; Sheng-Qi Zhou; Peng-Qi Huang; Xiao-Dong Shang; Jia-Jing Chen; Ze-Yao Weng; Wen-Dong Fang; Yuan-Zheng Lu; Guang-Hui Han (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

MXene-enhanced self-healing nanocomposite hydrogels with multiple-dynamic-bond crosslinking for motion sensing and information transmission - Ze-Hua Hou; Huan-Jie Che; Zi-Han Jiang; Xing Wu; Jin-Ping Yuan; Jing Li; Jian-Bo Qu (Chemical Engineering Journal, 2026)

Neuro-symbolic framework for multi-USV coordination: COLREGs-compliant and energy-efficient smart navigation - Shuai Huang; Yi-Feng Chen; Mao-Yuan Sun; Jia-Ning Gao; Yu-Han Zhou; Jing-Wen Zeng; Cheng-Chen Wang; Ya-Ze Han; Yang Xiong (Frontiers in Marine Science, 2026)
Introduction Coordinating multiple unmanned surface vehicles (USVs) in coastal waters requires simultaneous consideration of COLREGs compliance, real-time response, energy efficiency, fault tolerance, and semantic scene understanding. Existing approaches typically address only part of this problem and provide limited support for integrated fleet-level coordination. Methods This paper proposes NSC-Marine, a neuro-symbolic framework that conceptually addresses these coupled constraints. It combines multimodal causal perception, LLM-based rule reasoning, energy-aware motion planning, and distributed fault reconfiguration within a dual-rate control architecture. To improve deployment safety, semantic reasoning is used to generate structured constraints, while low-level motion execution remains under deterministic planning and control. Results The framework is evaluated strictly within a physics-based simulation environment with approximately 70% overall fidelity, involving 1,000 trials of 20–100 USVs under Beaufort Scale 3–5 conditions. Under these simulated conditions, NSC-Marine achieves 88.7% ± 2.3% COLREGs compliance, 82.3% mission success under compound faults, and 13.6% energy reduction relative to the RLCA baseline, while maintaining a 320 ms critical-path latency. Discussion These metrics reflect an idealized simulation baseline and must not be generalized to physical deployment readiness. Real-world performance remains unvalidated, and staged hardware-in-the-loop testing and field trials are required to characterize the system’s actual behavior under physical disturbances.

Mechanism of impact breakage in paddy rice: a cohesive zone model-based research on crack evolution and energy dissipation - Xianle Li; Anqi Li; Yanlong Han; Hao Li; Ze Sun; Haonan Gao; Xinlei Wang (Biosystems Engineering, 2026)

NPY-Y2R driven neuroimmune signaling as a potential therapeutic target for trigeminal neuralgia: clinical and experimental evidence - Zi-Le He; Chao Xu; Qi-Fan Yang; Cong-Zhou Han; Ting Wu; Yu-Qing Xu; Yun-Ze Liu; Liang-Yu Ni; Si-Qi Jia; Tang-Yu Zhang; Yun Wang; Yi Feng (Science Bulletin, 2026)

Collaborative optimization of hydraulic PTO parameters for a double floating WEC: Integrating orthogonal design and Bayesian optimization - Jianwei Wang; Jiachen Chai; Xinyu Han; Minghua Yue; Ze He; Rui Guo; Wei Cai (Ocean Engineering, 2026)

Dynamic responses of tension leg platforms considering the influence of tensioners based on a multi-stage feature extraction strategy - Jianwei Wang; Ze He; Minghua Yue; Lei Fan; Xinyu Han; Jiachen Chai; Xiaofan Jin (Ocean Engineering, 2026)

Dietary succinic acid supplementation enhances the growth performance and immunity of abalone Haliotis discus hannai - Ze Zhang; Zhenhua Wu; Xiaojun Yu; Tingting Fang; Ziqian Han; Yongqing Liu; Yang Liu; Kangsen Mai; Wenbing Zhang (Fish & Shellfish Immunology, 2026)

Sex-specific metabolic reprogramming in Trachinotus blochii under short- and long-term hypoxia - Yue Gu; Yue Chen; Ze Xin Zhong; Fu Cheng Yao; Chun Xiu Jin; Shan Ying Han; Fei Biao Song; Jian Luo; Jun Long Sun (Aquaculture, 2026)

Hydrogen-bonding guided isoreticular supramolecular frameworks with self-recovery for efficient natural gas purification - Zhou-Rui Yan; Xiao-Han Li; Shi-Kai Zheng; Ze-Jiu Diao; Fan Li; Jin-Peng Liu; Guoliang Liu; Lin-Bing Sun (Chemical Engineering Journal, 2026)

Prevalence and Molecular Characterization of Entamoeba spp. in Pigs in Shanxi Province, North China - Ze-Dong Zhang; Han-Dan Xiao; Dong-Yang Wang; Zi-Rui Wang; Xun-Zhi Liu; Nan Su; Xing-Quan Zhu; Qing Liu; Wen-Wei Gao (Acta Parasitologica, 2026)

Multiscale oceanic response to Typhoon Noru (2022) in the South China Sea: modulation by submesoscale processes - Dongmei Shen; Guoqing Han; Peiyu Liang; Jinyu Cai; Juncheng Xie; Peng Bai; Ze Meng; Yu Liu (Frontiers in Marine Science, 2026)
A comprehensive understanding of the upper-ocean response to typhoons is critical for improving typhoon intensity prediction. Although background mesoscale environments modulate the upper ocean, how submesoscale dynamics specifically drive the three-dimensional reshaping of the post-typhoon wake remains unclear. Our study employs a one-way nested model configuration (9 km parent grid and 3 km child grid) to examine the multiscale oceanic response to Typhoon Noru (2022) within the frontogenetic Vietnam Offshore Current region of the South China Sea. Mixed-layer heat budget analysis revealed that wind-driven vertical mixing primarily governed the forced-stage cooling magnitude, regardless of model resolution. However, the thermal evolution within the post-typhoon cold wake exhibited a pronounced contrast between the two resolutions. Spatial scale decomposition confirmed that the enhanced fine-scale thermal variability was primarily driven by submesoscale flows advecting background temperature gradients. Furthermore, the high-resolution simulation successfully resolved coherent ageostrophic secondary circulations along these submesoscale fronts. These localized overturning motions produced a persistent positive vertical buoyancy flux that slumped horizontal density fronts, thereby driving rapid restratification. These fine-scale vertical exchanges effectively transported warm surface water downward, governing the thermal restructuring within the post-typhoon cold wake. The findings highlight the importance of resolving submesoscale dynamics and provide a critical dynamical basis for improving sub-grid parameterizations of vertical transport in coupled prediction models.

Sex-specific responses of intestinal health, microbiota composition, and transcriptome profiles in golden pompano (Trachinotus blochii) subjected to hypoxia and reoxygenation - Xiao Kun Wang; Shan Ying Han; Ze Xin Zhong; Zeng Tan Hu; Tian Xiu Li; Yue Gu; Chun Xiu Jin; Tian Jiang; Fei Biao Song; Jian Luo; Jun Long Sun (Frontiers in Marine Science, 2026)
Introduction Driven by global climate change and coastal eutrophication, severe hypoxic events have become a primary environmental stressor in marine ecosystems, posing a critical threat to commercially vital teleosts like the golden pompano ( Trachinotus blochii ). Understanding the dimorphic physiological and microbial responses between sexes under such stress is crucial for developing targeted mitigation strategies. Methods Golden pompano were subjected to hypoxia stress (3.0 ± 0.2 mg/L) for 14 days, followed by restoration of dissolved oxygen to normoxic state (7.0 ± 0.2 mg/L) and cultivation for another 14 days. Subsequently, the histology ( n = 3), digestive enzyme activity ( n = 9), microbial composition ( n = 3), and transcriptome ( n = 3) of intestinal tissue were evaluated. Results Hypoxia induces marked physiological stress and a shift toward intestinal dysbiosis across both genders, manifested by damaged intestinal integrity, oxidative stress, and an increased abundance of opportunistic pathogens (e.g., Spirochaetes ). Although reoxygenation further deteriorates the histological condition of female intestinal tissue, it also triggers more significant molecular and enzyme activity rebound effects compared to males. Moreover, females exhibit significant upregulation of lipid metabolism, antioxidant defense mechanisms, and key signaling pathways, suggesting that they may have adopted a high-energy “compensatory recovery” strategy. Correlation analyses reveal that these microbial shifts are closely linked to host metabolic regulation: beneficial bacteria ( Pseudoalteromonas and Lactococcus ) support sterol transport and signaling homeostasis, while opportunistic taxa ( Brevinema ) negatively impact lipid synthesis. Discussion Our findings reveal a distinct gender dimorphism in the hypoxia and reoxygenation response, providing a theoretical foundation for sex-specific management and nutritional interventions in golden pompano aquaculture.

Shear wear effect on cross-fracture: coupled seepage and heat transfer evolution and prediction of unstable slip risk in geothermal reservoirs - Bowen Han; Shuhong Wang; Shiyu Li; Weiyi Wang; Ze Zhang (International Journal of Rock Mechanics and Mining Sciences, 2026)

Coordinating metabolic reprogramming and exosome secretion: A dual role for SIRT1/HIF-1α under hypoxia in golden pompano - Yue Chen; Shan Ying Han; Ze Xin Zhong; Chun Xiu Jin; Geng Hui Fang; Li Xiao Zhou; Fei Biao Song; Jian Luo; Jun Long Sun (Aquaculture, 2026)

Per-and poly-fluoroalkyl substances in lung tissues and their association with lung cancer - Xi-Ze Min; Li Ma; Fei Chen; Ying-Hua Hu; Chao Jiang; Yi-Fan Li; Yue Han; Zi-Feng Zhang; Kurunthachalam Kannan (Journal of Hazardous Materials, 2026)

Identification and validation of a QTL, QSNS.caas-3D.1, for spikelet number per spike in wheat - Xuezhong Liang; Junli Yang; Ze Liu; Fuping Zhang; Haiming Han; Shenghui Zhou; Jinpeng Zhang; Bing Han; Yida Lin; Hong-Qing Ling; Li Zheng; Junbo Yang; et al. (Theoretical and Applied Genetics, 2026)

Multiscale heat budget analysis of upper ocean responses to Typhoon Kalmaegi (2014) in the South China Sea - Jinyu Cai; Juncheng Xie; Ze Meng; Guoqing Han; Peng Bai; Yu Liu (Acta Oceanologica Sinica, 2026)

Differential enrichment mechanisms of organic matter in middle-upper Triassic lacustrine mudstone, north Kuqa depression (Tarim Basin, China): An integrated approach utilizing inorganic and organic geochemical evidence - Dejiang Li; Qun Zhao; Lingyu Zhao; Yanpeng Chen; Ze Deng; Xiangchun Chang; Bingbing Shi; Runye Han; Shangbin Wang (Acta Geochimica, 2026)

Study on GPR Forward Modeling and Intelligent Identification of Subgrade Defects Characterized by Hidden Voids - Bin Wu; Yan-li Qi; Qi-guang Cheng; Fan-meng Kong; Yu-xuan Han; Yiguo Xue; Yue-hua Wu; Sheng-yong Dong; Ze-zhou Kang; Zhe Zhang; Yong-feng Shi; Min Han (Applied Geophysics, 2026)

Effects of alfalfa as a substitute for dietary kelp on the growth, appetite, digestion, intestine histology, and immunity of abalone Haliotis discus hannai - Yongqing Liu; Zhenhua Wu; Xiaojun Yu; Ze Zhang; Tingting Fang; Yang Liu; Ziqian Han; Kangsen Mai; Wenbing Zhang (Aquaculture International, 2026)

Nickel refining fumes activate glutamine metabolism via the HIF‐1α/Notch pathway to drive epithelial-mesenchymal transition in Beas‐2B cells - Qian-Qian Sun; Han-Nong Yu; Rui-Ze Wu; Bo Zhang; Wen-Xue Yao; Wei-Yang Liu; Jia Han; Li-Yan Ju; Yu-Lin Pan; Yong-Hui Wu (Toxicology, 2026)

Interaction mechanism between two stages of separation explains residual rice husk formation in a multi-baffle separation duct - Shouyu Ji; Xianle Li; Dan Zhao; Hao Li; Ze Sun; Zhuozhuang Li; Anqi Li; Haonan Gao; Xinlei Wang; Yanlong Han; Fuguo Jia (Food and Bioproducts Processing, 2026)

Thermal-mechanical coupled vibration characteristics of a rotating FGP-GNPRC stepped cylindrical shell in nonlinear thermal environment - Ziyi Wang; Hui Li; Yufeng Chang; Qingpeng Han; Ze Jian; Yu Wang; Libo Cai (Engineering Structures, 2026)

Reprogramming lipid metabolism and morphology engineering in Yarrowia lipolytica for algae-free, high-titer production of esterified astaxanthin - Mo-Han Zhu; Hong-Ze Zhou; Zhijie Liu; Hong Zhu; Jun Chen; Chen Yang; Feng Liu; Qiang Hua (Chemical Engineering Journal, 2026)

A robust system for somatic embryogenesis and shoot organogenesis in Begonia grandis subsp. sinensis (A. DC.) Irmsch and genetic fidelity assessment of the regenerants - Feimin Ma; Zhengli Shan; Haonan Su; Ruijing Han; Wenjing Zhou; Mu Ze; Ming Dong; Qinggui Wu; Lijuan Zou (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Research on the impact of resident behavior on energy consumption during the heating period of ultra-low energy buildings - Ru-Xi Ding; Jia-Ze Dai; Ying-Nan Zhang; Xiao-Ping Wu; Cong-Han Yu; Zhenfa Fan (Energy and Buildings, 2026)

Closed-loop recycling and recovery of vanadium cathodes from waste aqueous zinc-ion batteries - Hsing-Kai Tseng; Jun-An Su; I-Mao Chen; Yu-Ze Chen; Jun-Yi Wu; Pin-Han Chen; Fan-Wei Liu (Chemical Engineering Journal, 2026)

Interpenetrated hierarchical polyzwitterionic hydrogels promote decellularized small-diameter vascular grafts regeneration - Qi-Ying Wu; Chun-Yang Chen; Jin-Chang Li; Ze-Guo Chen; Si-Cheng Chen; Chao Xie; Si-Xi Liu; Zi-Han Liu; Zhong-Shi Wu; Yu-Hong Liu (Chemical Engineering Journal, 2026)

Impacts of Sargassum hemiphyllum substitution for dietary kelp meal on the growth performance, muscle texture and immunity of abalone (Haliotis discus hannai) - Ziqian Han; Gaochan Qin; Zhenhua Wu; Xiaojun Yu; Ze Zhang; Tingting Fang; Yongqing Liu; Yang Liu; Kangsen Mai; Wenbing Zhang (Journal of Applied Phycology, 2026)

Dynamic health risk assessment of chromium exposure in soil and groundwater at tannery sites: a Bayesian network perspective - Shan-shan Guo; Yu Wang; Yong qiang Tian; Hao Wu; Yang Li; Xiao dan Jin; Xin Li; Ze-lin Zhou; Han Zhang; Jin-yan Yang (Environmental Geochemistry and Health, 2026)

Spatiotemporal Characteristics and Long-Term Variability of Large-Wave Frequency in the Northwest Pacific - Zhen-Yu Zhao; Hong-Ze Leng; Yu-Han Wei; Jin-Hui Yang; Xuan Zhou; Ze-Zheng Zhao; Hui-Peng Wang; Bao-Xu Li; Wu-Xin Wang; Jun-Qiang Song (Journal of Marine Science and Engineering, 2026)
This study provides a systematic analysis of the spatiotemporal distribution and trends in the frequency of significant wave height (SWH) exceeding level 5 (SWH > 2.5 m) and level 7 (SWH > 6 m) in the Northwest Pacific (NWP) for 1993–2024, which are defined as f5 and f7, respectively, as well as their correlations with major climate indexes. Our results indicate that (1) the high-value zones for the annual mean f5 and f7 are both located in the south waters of the Aleutian Islands, with maximum values of 58.0% and 6.4%, respectively. Winter’s contribution is greatest (maximum values of 96.9% and 16.8% per year), while summer’s is the smallest. (2) f5 exhibits a significant decline trend across the entire NWP basin (of −0.15 to −0.30%/yr), with the steepest decline occurring in autumn (−0.69%/yr) and the shallowest in summer. f7 exhibits a significant linear decrease in the open ocean east of Japan (−0.08%/yr) while showing a significant linear increase in the waters east of the Kamchatka Peninsula (0.08%/yr). Both variations peak in winter (maximum values of −0.27% and 0.30% per year) and are smallest in summer. (3) Seasonal and regional variations in climate index–f5 and f7 relationships reflect large-scale atmospheric modulation of waves. For example, the Oceanic Niño Index shows a predominantly negative correlation with f5 in winter (maximum correlation coefficient rm = −0.70) around the Luzon Strait, shifting to a significant positive correlation in summer (rm = 0.70) across the extensive region east of Taiwan Island and the Philippines. The Pacific Decadal Oscillation index shows a significant positive correlation with f7 in summer and autumn (rm = 0.69) east of Taiwan Island and a strong negative correlation in winter (rm = −0.77) to the east of Kamchatka Peninsula.

Evaluations on the regulation of resveratrol on the growth performance, anti-oxidation, immunity, heat tolerance and resistance to Vibrio parahaemolyticus of abalone Haliotis discus hannai - Xiaojun Yu; Zhenhua Wu; Ze Zhang; Tingting Fang; Ziqian Han; Yongqing Liu; Yang Liu; Kangsen Mai; Wenbing Zhang (Aquaculture, 2026)

Global grain crops non-CO2 greenhouse gas emissions and mitigation potential integrating food security and climate change scenarios - Yunxiao Gao; Ze Han; Zhihui Li; Xiangzheng Deng (Resources, Conservation and Recycling, 2026)

Naringenin as a bioactive preservative: Coordinated suppression of ethylene biosynthesis and cell wall disassembly delays apple senescence during storage - Ming-Fei Qiao; Peng-Liang Han; Meng-Meng Wei; Zhao-Peng Nie; Song Zhang; Wen-Yan Wang; Hai-Bo Wang; Tian-Ge Chu; Ze Chen; Quan Sun; Da-Gang Hu (Postharvest Biology and Technology, 2026)

Electrically insulating BNNS/PVDF@AlN/PVP composites with simultaneously enhanced in-plane and through-plane thermal conductivities - Wei-Hua Han; Yaping Fan; Yu Long; Bin Sun; Yun-Ze Long; Chun-Cheng Hao (Chemical Engineering Journal, 2026)

Developing sewage sludge hydrochar-based wood bio-adhesives: the role of oxidized lignin-containing cellulose nanofiber - Ze-Kai Tan; Han-Song Zhu; Fei Feng; Zu-Guo Yang; Li-Chun Dai; Zhi-Xiang Xu (Sustainable Chemistry and Pharmacy, 2025)

Micron-sized iron-sulfur minerals orchestrate micro-interface redox processes for sustainable wastewater treatment - Xin-Han Chen; Ze-Fan Chen; Chen-Peng Fang; Zhi-Zeng Zhao; Xiao-Qiang Cao; Jian Zhang; Zhao-Jing Zhu; Gang Zhou; Yi-Fan Wang; Lu-Cheng Fan; Li-Jiang Wu (Journal of Water Process Engineering, 2025)

Association between PM2.5 and its components and antral follicle count: A multicity study in Chinese adults - Ze Han; Jie Yin; Wangnan Cao; Qiang Zeng; Shengzhi Sun (Journal of Hazardous Materials, 2025)

Antioxidant and xanthine oxidase inhibitory theoretically evaluation of ferulic acid oligomers: Tetramers as outstanding dual-functional candidates - Qing-Hua Lu; Bai-Ze Liu; Jun Lu; Han Gao; Guo-Ze Wang; Jun-Li Lv; Xiao-Jun Li; Hui-Ying Peng (Food Bioscience, 2025)

Response of flow field and temperature field under shear behavior of heterogeneous fracture and discussion on wear characteristics - Bowen Han; Shuhong Wang; Ze Zhang; Meaza Girma; Furui Dong; Shixiong Ma (Bulletin of Engineering Geology and the Environment, 2025)

Application of a deep learning model with physical model constraints and attention mechanism for state prediction in high-power power-shift tractors - Li-quan Lu; Ze-peng Zhang; Guang-lin Zhang; Bing Han; Hao-ran Yang; Zhong-xiang Zhu; Zheng-he Song; Zhi-qiang Zhai; Jian-hua Wang; Chuan-chuan Zhang (Computers and Electronics in Agriculture, 2025)

4-Hydroxychalcone alleviated Angiotensin II-induced atrial fibrillation via immunoproteasome-IKK-NF-κB signaling pathway modulation - Yun-Long Zhang; Ze-Yan Xu; Yan Sun; Qian-Qiu Zhu; Sheng-Xing Tang; Qing-Hua Zhong; Xiao Han (Journal of Molecular Medicine, 2025)

Dietary dimethyl-β-propiothetine supplementation for abalone Haliotis discus hannai: effects on growth, digestion, immunity and appetite - Yang Liu; Zhenhua Wu; Xiaojun Yu; Peng Chen; Yongqing Liu; Ziqian Han; Ze Zhang; Tingting Fang; Kangsen Mai; Wenbing Zhang (Aquaculture International, 2025)

The potential of Cupriavidus sp. DF5525 degrading high concentrations of p-dichlorobenzene - Hong-Lin Ma; Ze-Shen Liu; Qun Han; Yi Yang; De-Feng Li (Journal of Hazardous Materials, 2025)

Numerical study on the influence mechanism of feed rate on separation quality in a multi-baffle separation duct - Shouyu Ji; Anqi Li; Yanlong Han; Hao Li; Ze Sun; Dan Zhao; Haonan Gao (Biosystems Engineering, 2025)

Numerical analysis and improvement method of screening effect during radial segregation of rice in the indented cylinder separator - Anqi Li; Xianzhi Hao; Yanlong Han; Hao Li; Shouyu Ji; Ze Sun; Zhuozhuang Li (Biosystems Engineering, 2025)

Numerical study on the transformation mechanism of rice discharging characteristics of double-orifice silo - Wenyu Feng; Yanlong Han; Anqi Li; Hao Li; Haonan Gao; Ze Sun; Yawen Xiao (Biosystems Engineering, 2025)

Effect of paddy grain flow behaviour on orientation adjustment mechanisms in rubber roll huller feeding chute - Hao Li; Yanlong Han; Dan Zhao; Jincheng Zhang; Anqi Li; Ze Sun; Shouyu Ji; Haonan Gao (Biosystems Engineering, 2025)

Design and experiment of a ridge-surface based cutting height active adjustment system for a leafy vegetable harvester - Haitao Peng; Zhiyu Zuo; Guoxin Ma; Luhua Han; Ze Liu; Hanping Mao (Biosystems Engineering, 2025)

Chitosan/PEO@Eu-MOF nanofiber membrane-based test strip for visual detection of tetracycline with smartphone-assisted analysis - Wei Pan; Zi-Han Zhu; Yan-Shen Zhao; Jie-Liu; Zhi-Guang Zhang; Gui-Xia Li; Tao Yu; Zhong-Zhi Han; Yun-Ze Long; Gui-Feng Yu (Chemical Engineering Journal, 2025)

Improved antifouling and regeneration capability of polyaniline-modified halloysite nanotube/MXene composite membranes - Jing-Yi Feng; Wen-Hao Geng; Ru-Yu Chang; Yu-Han Wang; Yue-Xin Wang; Ze-Long Bao; Wen-Yi Sun; Lu-Yao Tian; Di Zhang; Hong-Zhang Geng (Journal of Water Process Engineering, 2025)

Machine learning based prediction by PlantCdMiner and experimental validation of cadmium-responsive genes in plants - Chaoqun Xu; Ling Sun; Lu-Dan Zhang; Ze-Jun Guo; Ji-Cheng Wang; Li-Han Zhuang; Dong-Na Ma; Ling-Yu Song; Jing Li; Qian-Su Ding; Han-Chen Tang; Hai-Lei Zheng (Journal of Hazardous Materials, 2025)

Thick polyethylene films lessen pollution footprint while highlighting environmental merit and maize yielding in drylands - Xiao-Bin Xiong; Peng-Yang Wang; Ze-Ying Zhao; Zi-Yu Han; Yuan Song; Ying Zhu; Yi-Bo Wang; Jin-Lin Zhang; Xu-Sheng Guo; Xiao-Feng Zhang; Xiao-Yu Lu; You-Cai Xiong (Journal of Environmental Management, 2025)

Sand-manufactured sludge used as a component of passivators to remediate heavy metal contamination in acidic soil - Weiming Feng; Ze Zhang; Shi-wei Li; Xuemei Han; Yinghao Liu; Helian Li; Yuqing Zhang (Journal of Environmental Chemical Engineering, 2025)

Two new megastigmane glycosides from the leaves of Nicotiana tabacum and their anti-inflammatory activities - Peng-fei Yang; Wei Wu; Hang-hang Han; Qing-fu Wang; Lei Li; Ze-ning Wang; Duo-bin Mao; Zhi-fei Chen (Natural Product Research, 2025)

Genome-wide identification reveals a bZIP transcription factor modulating chlorophyll catabolism during leaf yellowing in harvested Chinese flowering cabbage - Ze-xiang Zeng; Yuan Rong; Zhong-qi Fan; Xin-guo Su; Lin Chen; Yan-chao Han; Hang-jun Chen; Wei Wei; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen (Postharvest Biology and Technology, 2025)

A weighted combination model for tensioner system prediction in floating platforms under internal waves - Jianwei Wang; Ze He; Xinyu Han; Jiachen Chai; Minghua Yue; Xiaofan Jin (Ocean Engineering, 2025)

Simultaneous high molecular weight PAHs degradation and chromate and arsenite detoxification by Altererythrobacter sp. H2 - Qun Han; Mei-Ling Yang; Ze-Shen Liu; Ying-Hao Zhao; Xue-Hui Liu; Guo-Min Ai; Wei-Hong Qin; Xing-Yu Liu; De-Feng Li (Journal of Hazardous Materials, 2025)

A hydrogel-based composite facilitates efficient and recyclable tetracycline biodegradation in aquatic environments - Ze-Hua Cui; Qian He; Zhi-Peng Li; Yao Deng; Xiao-Ping Liao; Chaoqun Zhang; Jian Sun; Hao Ren; Lu Han (Environmental Research, 2025)

Enoxacin-embedded EuMOF-based ratio fluorescent sensing platform integrated with paper-based sensor and skin-attachable hydrogel for glyphosate detection in foods - Liwei Bai; Ze Li; Qingju Liu; Zhikun Zhang; Heli Tian; Zhengjie Li; Jilong Han; Yongqi Hu (Journal of Hazardous Materials, 2025)

Konjac glucomannan and κ-carrageenan synergistically contribute to the cecal intestinal barrier function of offspring via improving the benefits of maternal milk - Wentao Zhang; Ze Wang; Junling Liu; Tingting Han; Guangmeng Lv; Baoming Shi; Feng Gao (Food Research International, 2025)

Late Pliocene lacustrine deposits expose the nonlinear response of the East Asian summer monsoon to insolation forcing - Zhixiang Wang; Ze Zhang; Mengmeng Cao; Haicheng Wei; Wenxia Han; Diederik Liebrand (Climate Dynamics, 2025)

Converting static to Dynamic: Biomimetic Ultra-Sensitive Wide-Range flexible pressure sensor inspired by the Contact-Regulation process of scorpion pectines - Junqiu Zhang; Jiachao Wu; Lili Liu; Xiangbo Gu; Xueping Zhang; Xueyang Li; Zijian Shi; Yu Chen; Jiqi Gao; Junfeng Zhang; Tao Sun; Honglie Song; et al. (Chemical Engineering Journal, 2025)

Mechanism of rice bran removal at individual grain and population levels in abrasive rice mill - Ze Sun; Xinlei Wang; Anqi Li; Jiaming Fei; Wenyu Feng; Dan Zhao; Yanlong Han; Fuguo Jia; Hao Li; Shouyu Ji; Zhuozhuang Li (Biosystems Engineering, 2025)

A method for influencing residential land population density by industrial development considering global and local scales: A case study of Wuzhong city, China - Yunxiao Gao; Ruimin Yin; Ying Wang; Ze Han; Xiangzheng Deng (Journal of Cleaner Production, 2025)

Peptide neurotoxins affecting insect voltage-gated calcium channels and possessing insecticidal toxicity: Two ω-Atypitoxins from Calommata signata - Yang-yang Yan; Kan Wang; Jing-ting Wang; Qian-qian Han; Zhen Zhang; Na Yu; Ze-Wen Liu (Pesticide Biochemistry and Physiology, 2025)

Targeted isolation of lignans and triterpenoids from kadsura coccinea by molecular networking and anti-RA-FLS activity - Shi-qi Liu; Qing-ling Xie; Ya-si Deng; Ling Liang; Han-wen Yuan; Bin Li; Huang-he Yu; Xing Tian; Yi-xing Qiu; Guy Paulin Kemayou Mouthe; Nuzhat Shehla; Ye Zhang; et al. (Phytochemistry, 2025)

A method for improving milling quality based on pre-milling in the combined rice milling process - Ze Sun; Anqi Li; Shouyu Ji; Hao Li; Zhuozhuang Li; Haonan Gao; Xinlei Wang; Xianle Li; Yanlong Han; Dan Zhao (Innovative Food Science & Emerging Technologies, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Vesicle-Shaped Co-Ni-S designed by first principles screening and d-Band center control for active hydrogen evolution - Youbin Zheng; Ze Li; Hao Guo; Cunyin Liu; Yuefeng Chen; Xiumei Han; Liang Dong; Jianbing Zang (Fuel, 2025)

Techno-economic evaluation and multi-objective optimization of a cogeneration system integrating solid oxide fuel cell with steam Rankine and supercritical carbon dioxide Brayton cycles - Zihao Huang; Huailiang You; Jitian Han; Guoxiang Li; Yan Xiao; Bin Hu; Ze-Hang Chen; Daifen Chen (Fuel, 2025)

Salinity affects C/N ratio through differential responses of carbon and nitrogen metabolism in mangrove Avicennia marina leaves revealed by combined analysis of transcriptome and metabolome - Jing Li; Ling-Yu Song; Ze-Jun Guo; Chao-Qun Xu; Lu-Dan Zhang; Ji-Cheng Wang; Han-Chen Tang; Ming-Jin Dai; Xue-Yi Zhu; Hai-Lei Zheng (Plant and Soil, 2025)

Effects of Encarsia formosa (Hymenoptera: Aphelinidae) parasitism on the feeding preference and performance of the whitefly predator Serangium japonicum (Coleoptera: Coccinellidae) - Yi-Han Li; Ze-Yun Fan; Zhan-Peng Zhu; Xiao-Lu Lv; Muhammad Musa Khan; Jing-Chen Sun; Bao-Li Qiu (Crop Protection, 2025)

Bismuth/manganese-doped carbon dots in calcium phosphate matrix: Dynamic conformational nanoparticles enhancing tumor accumulation, deep penetration, and radiosensitivity - Jiahao Liu; Qingnian Li; Hanyu Tu; Jie Feng; Xiaofei Fan; Ze Mi; Hongpei Han; Xiaoqian Ma; Qi Liang; Zheng Zhang; Hongshuai Hou; Pengfei Rong; et al. (Chemical Engineering Journal, 2025)

Investigation of rice debranning mechanism based on tribological behaviour between rice grains - Jiaming Fei; Ze Sun; Dan Zhao; Anqi Li; Fuguo Jia; Yanlong Han; Hao Li; Shouyu Ji; Zhuozhuang Li; Wenyu Feng (Biosystems Engineering, 2024)

Leaching behavior and release mechanism of pollutants from different depths in a phosphogypsum stockpile - Han Ke; Shu Ning Zheng; Peng Ze Zhang; Bo Xiao; Ji Wu Lan; Shuai Zhang; Jie Hu (Waste Management, 2024)

Phosphocreatine ameliorates hepatocellular apoptosis mediated by protecting mitochondrial damage in liver ischemia/reperfusion injury through inhibiting TLR4 and Agonizing Akt Pathway - Fu Han Wang; Eskandar Qaed; Waleed Aldahmash; Mueataz A. Mahyoub; Zhongyuan Tang; Peng Chu; Ze Yao Tang (Tissue and Cell, 2024)

Exposure to ambient particulate matter and ovarian reserve impairment among reproductive age women in China - Ze Han; Jiayi Liu; Tian Liang; Jie Yin; Jing Wei; Qiang Zeng; Wangnan Cao; Changjiang Liu; Shengzhi Sun (Journal of Hazardous Materials, 2024)

Optimizing ABA-based chemically induced proximity for enhanced intracellular transcriptional activation and modification response to ABA - Zeng Zhou; Yue-Qi Wang; Xu-Nan Zheng; Xiao-Hong Zhang; Lu-Yao Ji; Jun-You Han; Ze-Cheng Zuo; Wei-Liang Mo; Li Zhang (Science China Life Sciences, 2024)

A material point method analysis of failure mechanism and kinematic behavior of rainfall-induced landslide - Shuhong Wang; Meaza Girma Demisa; Bowen Han; Qinkuan Hou; Ze Zhang (Natural Hazards, 2024)

Loss of TET Activity in the Postnatal Mouse Brain Perturbs Synaptic Gene Expression and Impairs Cognitive Function - Ji-Wei Liu; Ze-Qiang Zhang; Zhi-Chuan Zhu; Kui Li; Qiwu Xu; Jing Zhang; Xue-Wen Cheng; Han Li; Ying Sun; Ji-Jun Wang; Lu-Lu Hu; Zhi-Qi Xiong; et al. (Neuroscience Bulletin, 2024)

Reason and control strategy for denitrification and anammox sludge flotation in nitrogen removal process: Mechanisms, strategies and perspectives - Xin Ma; Xin-Rui Zhang; Ying-Jun Sun; Zhi-Han Xi; Jin-Ze Liu; Ze-Tong Feng; Jia-Min Zhou; Xin-Tao Liu; Ying Wang; Ren-Cun Jin; Qian-Qian Zhang (Environmental Research, 2024)

Chemical constituents from Elephantopus scaber L. and their chemotaxonomic significant - Ze-Ming Wu; Mei-Ya Lian; Xiao-Yu Han; Ming Bai; Shao-Jiang Song (Biochemical Systematics and Ecology, 2024)

Tracing residual patterns and microbial communities of pharmaceuticals and personal care products from 17 urban landfills leachate in China - Lin-Hui Zhang; Jin-Nong Li; Yi-Hao Li; Xi-Ze Min; De-Yong Kong; Yue Han; Chao Jiang; Hang Xiao; Bin Liang; Zi-Feng Zhang (Journal of Hazardous Materials, 2024)

Multi-omics insights into the function and evolution of sodium benzoate biodegradation pathway in Benzoatithermus flavus gen. nov., sp. nov. from hot spring - Chao-Jian Hu; Yi-Qing Lv; Wen-Dong Xian; Jian-Yu Jiao; Zheng-Han Lian; Sha Tan; Meng-Meng Li; Zhen-Hao Luo; Ze-Tao Liu; Ai-Ping Lv; Lan Liu; Mukhtiar Ali; et al. (Journal of Hazardous Materials, 2024)

The effectiveness of gliding arc discharge plasma in sterilizing artificial seawater contaminated with Vibrio parahaemolyticus - Meng-Ru Du; Yu-yi Guo; Han-ze Wei; Yu-pan Zhu; Rong-rong Liu; Ruo-nan Ma; Fu-kun Shi; Jin-song Guo; Jie Zhuang (Journal of Hazardous Materials, 2024)

Simultaneous removal of nitrate nitrogen and ammonium nitrogen by partial denitrification coupled with anammox synergy by zero-valent iron - Jia-Min Zhou; Ying-Jun Sun; Zhi-Han Xi; Zu-Gang Liao; Xin Ma; Ze-Tong Feng; Xin-Tao Liu; Xin-Rui Zhang; Ying Wang; Ying Chen; Ren-Cun Jin; Qian-Qian Zhang (Journal of Cleaner Production, 2024)

Exogenous sulfur application can effectively alleviate iron deficiency yellowing in peanuts and increase pod yield - Xiao-yan Zhang; Wen-feng Hou; Ze-chang Gou; Shu-ran Jia; Han Li; Qiang Gao; Xiao-yu Li (European Journal of Agronomy, 2024)

Bulky neutral group incorporation in Through-Space charge transfer delayed fluorescence emitters for efficient Non-Doped organic Light-Emitting diodes - Han-Yang Wang; Feng-Ming Xie; Hao-Ze Li; Kai Zhang; Jianhua Zou; Yan-Qing Li; Jian-Xin Tang (Chemical Engineering Journal, 2024)

Association between residential greenness and incident delirium: A prospective cohort study in the UK Biobank - Qida He; Mengtong Sun; Yu Wang; Guoxian Li; Hanqing Zhao; Ze Ma; Zhaolong Feng; Tongxing Li; Qiang Han; Na Sun; Linyan Li; Yueping Shen (Science of The Total Environment, 2024)

Sphingobium sp. SJ10-10 encodes a not-yet-reported chromate reductase and the classical Rieske dioxygenases to simultaneously degrade PAH and reduce chromate - Ze-Shen Liu; Ke-Huan Wang; Qun Han; Cheng-Ying Jiang; Shuang-Jiang Liu; De-Feng Li (Journal of Hazardous Materials, 2024)

Tectochrysin ameliorates dextran sulfate sodium-induced chronic colitis by regulating the intestinal flora and inflammatory responses - Qifeng Yu; Shiguang Yang; Yujiao Han; Xiang Wang; Ningbo Xiao; Ze Yu; Jinliang Dong (Food Bioscience, 2024)

Genome-wide identification, characterization, molecular evolution and expression profiling analysis of scavenger receptors in black rockfish (Sebastes schlegelii) - Zhentao Chen; Xuangang Wang; Gan Yu; Jingrun Pu; Xuechen Li; Ze Tao; Zhixiang Duan; Fan Zhang; Ping Han; Hengshun Li; Haiyang Yu (Fish & Shellfish Immunology, 2024)

Mitigation Effect of Exogenous Dopamine Treatment on Downy Mildew-Infected Cucumber - Ze-Yu Ji; Ze-Yu Liu; Li-Ming Shi; Xin-Yu Lu; Yu-Ying Han; Yan Sun (Journal of Plant Growth Regulation, 2024)

Two new steroids with cytotoxicities from fungus Acrocalymma cycadis - Li-Bin Lin; Deng-Gao Zhu; Ting Yang; Rui Han; Jia-Yao Hu; Wei Shi; Ze-Yi Li; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2024)

Extending the freshness of tilapia surimi with pulsed electric field modified pea protein isolate-EGCG complex - Zhong Han; Ze-Ling Chen; Xin-Dong Xu; Songyi Lin; Yan Wang; Lang-Hong Wang; De-Bao Niu; Xin-An Zeng; Meng-Wai Woo; Ruo-Yong Wang (Food Hydrocolloids, 2024)

Integration of transcriptome, gut microbiota, and physiology reveals toxic responses of the red claw crayfish (Cherax quadricarinatus) to imidacloprid - Yao-Peng Lu; Jia-Han Liu; Xiu-Xia Zhang; Chi Xu; Pei-Hua Zheng; Jun-Tao Li; Jia-Jun Li; Dong-Mei Wang; Jian-An Xian; Ze-Long Zhang (Journal of Hazardous Materials, 2024)

Assessment of natural resource endowment and urban-rural integration for sustainable development in Xinjiang, China - Keqiao Su; Dawei He; Ruixue Wang; Ze Han; Xiangzheng Deng (Journal of Cleaner Production, 2024)

The impact of cross-regional social and ecological interactions on ecosystem service synergies - Ze Han; Xiangzheng Deng (Journal of Environmental Management, 2024)

Optimization of alkaline hydrothermal treatment for humic acids production from corn straw digestate using the response surface methodology - Shuai-Ze Han; Bo-Tao Zhang; Man-Qian Wang; Rong-Bo Guo; Shan-Fei Fu (Journal of Environmental Chemical Engineering, 2024)

TEAOH-assisted cost-effective preparation of SSZ-13 using L zeolite as Al source - Zongyang Zhang; Yuping Li; Ze Chen; Fuchao Ji; Xiaohong Liang; Haicheng Xuan; Lina Han; Peide Han (Fuel, 2024)

Highly efficient and selective electrosynthesis of urea via co-reduction of carbon dioxide and nitrate over the TiN catalyst - Hongjun Fang; Ze Wang; Chen-Han Kuo; Hongsheng Yang; Xinzhen Feng; Weijie Ji; Chak-Tong Au (Chemical Engineering Journal, 2024)

Research on CO2 capture performance and reaction mechanism using newly tetraethylenepentamine (TEPA) + monoethanolamine (MEA) mixed absorbent for onboard application - Song Zhou; Yunlong Zhu; Hongyuan Xi; Ze Hao; Zhitao Han; Chengqi Sun (Chemical Engineering Journal, 2024)

Whole genome sequencing analysis of Limosilactobacillus reuteri from the intestinal tract of mice recovering from ulcerative colitis and preliminary study on anti-inflammatory effects of its derived peptides - Ziyan Wang; Zhixuan Zhang; Qiuyue Shi; Songyi Liu; Qiaoli Wu; Ze Wang; Emilaguli saiding; Jiaojiao Han; Jun Zhou; Rixin Wang; Xiurong Su (Archives of Microbiology, 2024)

Electron beam irradiation pretreatment for efficient extraction of pectin from spaghetti squash peel: Structural, functional, and biological properties - Hui Han; Yi Luo; Junqing Bai; Ze Tao; Shuo Wang; Xiaoqing Lei; Yuxin Feng; Yamei Ren (Food Hydrocolloids, 2024)

Analysis of antimicrobial biological activity of a marine Bacillus velezensis NDB - Ze Wang; Wenwen Zhang; Ziyan Wang; Zhixuan Zhang; Yan Liu; Songyi Liu; Qiaoli Wu; Emilaguli Saiding; Jiaojiao Han; Jun Zhou; Jiajie Xu; Xianghua Yi; et al. (Archives of Microbiology, 2024)

Conservation or deforestation: Households attitudinal analysis of forest resources for sustainable development of the Tain (II) Forest Reserve, Ghana - Michael Asiedu Kumi; Zheng Yang; Jinyan Zhan; Wei Liu; Huihui Wang; Yufei He; Louis Addae-Wireko; Susana Addae-Wireko; Samuel Yeboah; Emmanuel Kombiok; Han Ze (Environmental Science & Policy, 2024)

α-Glucan derivatives as selective blockers of aldolase A: Computer-aided structure optimization and the effects on HCC - Qian-Han Xiao; Ze-Zhi Li; Li Ren; Shu-Yao Wang; Xiao-Qiang Li; Hong-Xin Bai; Rui-Zhi Qiao; Na Tang; Wen-Juan Liu; Jing-Mei Wang; Guang-Yuan Ma; Dian-Chao Dong; et al. (Carbohydrate Polymers, 2024)

Neogene morphotectonic evolution of the East Asian Continental Shelf - Haohao Cheng; Yanhui Suo; Xuesong Ding; Sanzhong Li; Ze Liu; Syed Wajid Hanif Bukhari; Guangzeng Wang; Pengcheng Wang; Liangliang Wang; Hao Dong; Xianzhi Cao; Xu Han; et al. (Geomorphology, 2024)

Contrasting behavior of K isotopes in modern and fossil groundwater: Implications for K cycle and subsurface weathering - Tao-Tao Ji; Xiao-Wei Jiang; Guilin Han; Xiaoqiang Li; Li Wan; Ze-Zhou Wang; Huaming Guo; Zhangdong Jin (Earth and Planetary Science Letters, 2024)

Simulation of the movement of rice grains in a centrifugal huller by discrete element method and the influence of blade shape - Anqi Li; Fuguo Jia; Yanhao Chu; Yanlong Han; Hao Li; Ze Sun; Shouyu Ji; Zhuozhuang Li (Biosystems Engineering, 2023)

Classification of Glomerular Pathology Images in Children Using Convolutional Neural Networks with Improved SE-ResNet Module - Xiang-Yong Kong; Xin-Shen Zhao; Xiao-Han Sun; Ping Wang; Ying Wu; Rui-Yang Peng; Qi-Yuan Zhang; Yu-Ze Wang; Rong Li; Yi-Heng Yang; Ying-Rui Lv (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Non-uniform milling caused by preferential orientation of rice grains in friction rice mills - Jiaming Fei; Wenyu Feng; Shaohang Shen; Yanlong Han; Anqi Li; Xianzhi Hao; Fuguo Jia; Ze Sun; Shouyu Ji; Zhuozhuang Li (Biosystems Engineering, 2023)

The abnormal track of super typhoon Hinnamnor (2022) and its interaction with the upper ocean - Huipeng Wang; Jiagen Li; Junqiang Song; Hongze Leng; Huizan Wang; Ze Zhang; Han Zhang; Minglin Zheng; Xiangrong Yang; Chunming Wang (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Low-temperature sintering of multifunctional SiC catalytic membrane for synergistic emission control of toluene and dust - Jiahao Chen; Yiqing Zeng; Yongliang Yin; Yarong Fang; Feng Han; Ze-Xian Low; Zhaoxiang Zhong; Weihong Xing (Chemical Engineering Journal, 2023)

Electrochemical oxidation treatment of reverse osmosis concentrated landfill leachate: Effect of operation parameters and evolution of dissolved organic matter - Ye-Chao Tian; Wen-Xiang Ji; Yu-Ze Han; Ze-Tao Wu; Hai-Ou Song; Ai-Min Li; Wen-Tao Li (Chemical Engineering Journal, 2023)

Ent-eudesmane sesquiterpenoids from the Chinese liverwort Chiloscyphus polyanthus - Ming-Zhu Zhu; Yi Li; Jin-Chuan Zhou; Dong-Xue Lv; Xiao-Jie Fu; Zhen Liang; Shuang-Zhi Yuan; Jing-Jing Han; Jiao-Zhen Zhang; Ze-Jun Xu; Wen-Qiang Chang; Hong-Xiang Lou (Phytochemistry, 2023)

A novel method for solidification/stabilization of MSWI fly ash by graphene nanoplatelets synergistic alkali-activated technology - Tianru Li; Baomin Wang; Xiong Zhang; Xiao Han; Yunqing Xing; Chengcheng Fan; Ze Liu (Journal of Environmental Chemical Engineering, 2023)

Characterization and fitness cost analysis of two plasmids carrying different subtypes of bla in aquaculture farming - Yaru Zhang; Dingting Xu; Ze He; Jianzhong Han; Daofeng Qu (Food Microbiology, 2023)

Impacts of cross-regional population migration and agglomeration on carbon emissions in China - Ze Han; Xiangzheng Deng (Applied Geography, 2023)

Reduction potential of vehicular emission in Chengdu, China: A case study of COVID-19 - Xinping Yang; Hefeng Zhang; Wei Li; Hong Tian; Yongdong Wang; Jing Zhou; Ze Bao; Xiaorui Chen; Teng Xiao; Yunjing Wang; Mingliang Fu; Xian Wu; et al. (Urban Climate, 2023)

Role of Mutations of Mitochondrial Aminoacyl-tRNA Synthetases Genes on Epileptogenesis - Ling-yue Kong; Yi-ze Wu; Run-qi Cheng; Pei-han Wang; Bi-wen Peng (Molecular Neurobiology, 2023)

Hydrodynamic and anthropogenic disturbances co-shape microbiota rhythmicity and community assembly within intertidal groundwater-surface water continuum - Ze Zhao; Lu Zhang; Guoqing Zhang; Han Gao; Xiaogang Chen; Ling Li; Feng Ju (Water Research, 2023)

Effect of nano silica on solidification/stabilization of heavy metal in alkali-activated MSWI fly ash solidified body - Tianru Li; Baomin Wang; Xiong Zhang; Xiao Han; Yunqing Xing; Chengcheng Fan; Ze Liu (Process Safety and Environmental Protection, 2023)

Pallamins A–C, ent-labdane and pallavicinin based dimers from the Chinese liverwort Pallavicinia ambigua (mitt.) stephani - Yi Li; Xiao-Bin Li; Jin-Chuan Zhou; Ze-Jun Xu; Ming-Zhu Zhu; Yan Zong; Jiao-Zhen Zhang; Jing-Jing Han; Ya-Jie Tang; Hong-Xiang Lou (Phytochemistry, 2023)

Mesomechanical characteristics of rock failure under variable amplitude cyclic loading by DEM - Ze-han Liu; Jin Yu; Chong-hong Ren; De-fu Zhu; Xiao-qin Chen (Bulletin of Engineering Geology and the Environment, 2023)

Machine learning-aided scoring of synthesis difficulties for designer chromosomes - Yan Zheng; Kai Song; Ze-Xiong Xie; Ming-Zhe Han; Fei Guo; Ying-Jin Yuan (Science China Life Sciences, 2023)

Microplastics exacerbate co-occurrence and horizontal transfer of antibiotic resistance genes - Xi Yu; Zhen-Chao Zhou; Xin-yi Shuai; Ze-jun Lin; Zhe Liu; Jin-yu Zhou; Yan-han Lin; Guang-shu Zeng; Zi-ye Ge; Hong Chen (Journal of Hazardous Materials, 2023)

Extreme multistability and phase synchronization in a heterogeneous bi-neuron Rulkov network with memristive electromagnetic induction - Quan Xu; Tong Liu; Shoukui Ding; Han Bao; Ze Li; Bei Chen (Cognitive Neurodynamics, 2023)

Unraveling the evolution of dissolved organic matter in full-scale A/A/O wastewater treatment process using size exclusion chromatography with PARAFAC and nonnegative matrix factorization analysis - Min-Hui Cai; Ye-Chao Tian; Ai-Min Li; Yan Li; Yu-Ze Han; Wen-Xiang Ji; Qing Zhou; Jun Li; Wen-Tao Li (Water Research, 2023)

Bionic multifunctional ultra-linear strain sensor, achieving underwater motion monitoring and weather condition monitoring - Jianhao Li; Zhongwen Yao; Xiangxiang Zhang; Ze Wang; Linpeng Liu; Xiaoning Yang; Junqiu Zhang; Shichao Niu; Zhiwu Han; Luquan Ren (Chemical Engineering Journal, 2023)

Changes of dissolved organic matter fractions and formation of oxidation byproducts during electrochemical treatment of landfill leachates: Development of spectroscopic indicators for process optimization - Bi-Cun Jiang; Ye-Chao Tian; Ai-Min Li; Yu-Ze Han; Ze-Tao Wu; Chang Lu; Hai-Ou Song; Rong Ji; Wen-Tao Li; Gregory V. Korshin (Water Research, 2023)

Eliminating temporal correlation in quantum-dot entangled photon source by quantum interference - Run-Ze Liu; Yu-Kun Qiao; Han-Sen Zhong; Zhen-Xuan Ge; Hui Wang; Tung-Hsun Chung; Chao-Yang Lu; Yong-Heng Huo; Jian-Wei Pan (Science Bulletin, 2023)

Proteomic analysis reveals differential responsive mechanisms in Solanum nigrum exposed to low and high dose of cadmium - Ling-Yu Song; Xiang Liu; Lu-Dan Zhang; Wen-Jun Hu; Chao-Qun Xu; Jing Li; Shi-Wei Song; Ze-Jun Guo; Chen-Yang Sun; Han-Chen Tang; Ji-Cheng Wang; Xue-Yi Zhu; et al. (Journal of Hazardous Materials, 2023)

Evaluation of BDE-47-induced neurodevelopmental toxicity in zebrafish embryos - Juan Zhuang; Zheng-jun Pan; Ying Qin; Hui Liang; Wen-feng Zhang; Ze-yu Sun; Han-bo Shi (Environmental Science and Pollution Research, 2023)

Changes in China’s food security driven by nutrition security and resource constraints - Ze Han; Xinqi Zheng; Lingling Hou; Nan Xiao; Xiangzheng Deng (Environment, Development and Sustainability, 2023)

Co-substrate promoting the biodegradation of refractory DOM in semi-coking wastewater: DOM evolution and microbial community - Min-Hui Cai; Ye-Chao Tian; Ai-Min Li; Yan Li; Yu-Ze Han; Jun Li; Hong-Fang Sun; Xin Wang; Qing Zhou; Wen-Tao Li (Journal of Environmental Chemical Engineering, 2023)

Multi-index assessment of heavy metal contamination in surface sediments of the Pearl River estuary intertidal zone - Rui-Ze Liang; Yang-Guang Gu; Hai-Song Li; Yan-Jie Han; Jie Niu; Hong Su; Richard W. Jordan; Xiang-Tian Man; Shi-Jun Jiang (Marine Pollution Bulletin, 2023)

Reduced carbon footprint inequality in China: Evidence from latest household survey data - Maolin Liao; Jin Jia; Guoying Han; Guofeng Wang; Ze Zhang; Gang Wu (Journal of Cleaner Production, 2023)

Noble-metal-free 3D hierarchical Ni-WC heterostructure with enhanced interfacial charge transfer for efficient electrocatalytic hydrodechlorination - Qi Wang; Jing Du; Yuan-Yuan Ma; Xiao-Yu Yin; Ze-Yu Tian; Zhan-Gang Han (Chemical Engineering Journal, 2023)

Shift work and nonalcoholic fatty liver disease incidence among Chinese rail workers: a 4-year longitudinal cohort study - Jiahui Xu; Shu Ni; Yuming Wang; Mengfan Yan; Xueli Yang; Han Ge; Zizhuo Jia; Ze Yang; Anqi Shan; Huanyu Liu; Nai-jun Tang (International Archives of Occupational and Environmental Health, 2023)

Effects of dietary glutathione on the growth performance, skin mucus antioxidant capacity, and immune responses of juvenile taimen Hucho taimen - Chang’an Wang; Shaoxia Lu; Ze Fan; Shicheng Han; Yang Liu; Haibo Jiang; Hongbai Liu (Aquaculture International, 2022)

Rose Bengal inhibits β-amyloid oligomers-induced tau hyperphosphorylation via acting on Akt and CDK5 kinases - Chen-Ye Mou; Yan-Fei Xie; Jia-Xin Wei; Qi-Yao Wang; Jing-Yang Le; Yong-Jie Bao; Pan-Pan Zhang; Yue-Chun Mao; Xing-Han Huang; Han-Bo Pan; C. Benjamin Naman; Lin Liu; et al. (Psychopharmacology, 2022)

Evaluation of the Potential of the Hard Clam (Meretrix meretrix) Shell Which Can Be Used as the Bioindicator for Heavy Metal Accumulation - Yen-Ting Lin; Fang-Chi Chang; Ming-Tsung Chung; Ze-Kai Li; Chang-Chuan Chan; Ying-Sheng Huang; Kuo-Fang Huang; Yu-San Han (Fishes, 2022)
Clams, Meretrix meretrix, were one of the favorite aquatic products in Taiwan and the world. It was reported that the water pollutants such as heavy metals and chemicals might accumulate in the clam body and shell through filter-feeding behavior. Thus, the bivalves could be used as bioindicators in the aquatic environment. The present study analyzed 20 trace elements, Mg, Sr, Li, Cd, Ba, Mn, Al, U, Ti, Pb, Nd, B, S, Zn, Fe, P, Na, K, Cu, and Ni, in the shells of the clams collected from the wild coastal area and cultured ponds to evaluate which elements have the potential to be biomarkers. The concentrations of 20 elements were detected by Solution-Based Inductively Coupled Plasma Mass Spectrometry (SB-ICPMS). Among them, Cd, Al, U, Ti, Nd, S, and K were below the detection limit. The remaining elements were analyzed for accumulation. The levels of Zn, Fe, and Ni possess high variation in an identical environment; so, a PCA was conducted without these three elements to reduce noise. The PCA result proved that the clam could absorb specific trace elements from the habitat. After a period of time, the contents of the absorption in the shells of the clams living in an identical environment became more similar. The analyzed element, Pb, was not found with a special difference in this study. The levels of Na, Sr, Mg, B, Mn, P, Ba, Li, and Cu reflected different sampling sites, which suggested that these elements in the species M. meretrix had the potential to be used as biomarkers for assessing heavy metal accumulation in the environment.

Long-term exposure to PM2.5 and PM10 and chronic kidney disease: the Beijing Health Management Cohort, from 2013 to 2018 - Lulu Liu; Xue Tian; Yuhan Zhao; Zemeng Zhao; Lili Luo; Hui Luo; Ze Han; Xiaoping Kang; Xiaonan Wang; Xiangtong Liu; Xiuhua Guo; Lixin Tao; et al. (Environmental Science and Pollution Research, 2022)

Paracandidimonas lactea sp. nov., a urea-utilizing bacterium isolated from landfill - Chu Zhang; Qian Pu; Jun-jie Ying; Ying Chen; Cheng-ze Li; Hang-tao Wu; Bin-jie Wang; Yu-han Zhang; Guo-hong Zeng; Ou Li; Xiu-fang Hu; Cong Sun (Archives of Microbiology, 2022)

Validity Analysis of the Morphological Identification of Three Highly Morphologically Similar Species Belonging to the Genus Niviventer (Rodentia: Muridae) - Yao-Yao Li; Hao-Tian Li; Jia-Wei Hao; Chen-Yi Zhang; Guan-Ze Liu; Xing-Han Lin; Xiao-Qing Sun; Guo-Chen Zang; Yu-Chun Li (Journal of Mammalian Evolution, 2022)

Research of Intelligent Logistics and High-Quality Economy Development for Yangtze River Cold Chain Shipping Based on Carbon Neutrality - Ruiqi Xiao; Lin Pan; Hanbin Xiao; Han Xiao; Ze Zhu (Journal of Marine Science and Engineering, 2022)
The current status of intelligent logistics and cold chain shipping research is a hot topic worldwide. Meanwhile, the study of regional logistics and regional economy, shipping logistics and regional economic theory and application methods, and the empirical analysis of the correlation between the Yangtze River shipping and the Yangtze River shipping economy have attracted a lot of attention. This research has revealed that the Internet of Things of Yangtze River shipping has a great impact on the Yangtze River and the importance of inland river economic development. This study presents the empirical analysis on the correlation between shipping logistics and the inland river economy, starting from qualitative and quantitative aspects, and taking Yangtze River shipping as the representative. The proposed mathematical models and qualitative data analysis are made on the relevant effects of intelligent logistics and cold chain shipping on an inland river economy including its impact on the industrial layout, international trade, and urbanization. The research results provide administrative decisions or guidance values for the economic development of inland river ports in the Yangtze River.

A field test to investigate spatiotemporal distribution of soil moisture under different cropland covers in the semiarid Loess Plateau of China - Ze-Jun Han; Ding-Feng Cao; Hong-Hu Zhu; Bing Wu; Jia-Chen Wang; Sanjay Kumar Shukla (Paddy and Water Environment, 2022)

Grain size-dependent geochemical evidence reveals provenance and implications of aeolian sands, Dinggye region, southern Tibet - You-gui Chen; Mei-hui Pan; Ze-wen Hao; Yu-han Qi; Chen-lu Li (Journal of Mountain Science, 2022)

Rhodoflexus caldus gen. nov., sp. nov., a new member of the phylum Bacteroidota isolated from a hot spring sediment - Ze-Tao Liu; Lan Liu; Wen-Dong Xian; Zheng-Han Lian; Jun-Yi Dai; Bao-Zhu Fang; Meng-Meng Li; Ai-Ping Lv; Zhen-Hao Luo; Jian-Yu Jiao; Wen-Jun Li (Antonie van Leeuwenhoek, 2022)

Genome-wide characterization and expression analysis of SAUR gene family in Melon (Cucumis melo L.) - Ze Tian; Jiadi Han; Gen Che; Agula Hasi (Planta, 2022)

Genome-based reclassification of the genus Meiothermus along with the proposal of a new genus Allomeiothermus gen. nov - Jian-Yu Jiao; Zheng-Han Lian; Ze-Tao Liu; Lan Liu; Meng-Meng Li; Ai-Ping Lv; Wen-Dong Xian; Ting Zhou; Zhitang Lyu; Nimaichand Salam; Wen-Jun Li (Antonie van Leeuwenhoek, 2022)

MicroRNA-451a attenuates angiotensin II–induced cardiac fibrosis and inflammation by directly targeting T-box1 - Hao-Yuan Deng; Ze-Yin He; Zhi-Chao Dong; Yun-Long Zhang; Xiao Han; Hui-Hua Li (Journal of Physiology and Biochemistry, 2022)

Two new nor -lignans from Selaginella pulvinata (Hook. & Grev.) Maxim and their antihyperglycemic activities - Hua-Wei Lv; Yu-Xia Li; Meng Luo; Jia-Meng Qi; Ze-Fei Fu; Hong-Jian Zhang; Yuan-Qiang Guo; Chu Chu; Han-Bing Li; Ji-Zhong Yan (Natural Product Research, 2022)

CRISPR-Cas systems are present predominantly on chromosome and its relationship with MEGs in Vibrio species - Enbao Zhang; Wei Zhou; Jinzhi Zhou; Ze He; Yuqiao Zhou; Jianzhong Han; Daofeng Qu (Archives of Microbiology, 2022)

Maribellus maritimus sp. nov., isolated from marine sediment - Yu-Qi Ye; Ze-Tian Han; Xin-Jiang Liu; Meng-Qi Ye; Zong-Jun Du (Archives of Microbiology, 2022)

Loganin ameliorates depression-like behaviors of mice via modulation of serotoninergic system - Chen-Hao Pan; Cong-Yuan Xia; Yu Yan; Yan Han; Rui Shi; Jun He; Ze-Xing Wang; Yu-Ming Wang; Wei-Ku Zhang; Jie-Kun Xu (Psychopharmacology, 2021)

A network pharmacology study with molecular docking to investigate the possibility of licorice against posttraumatic stress disorder - Zhi-Kun Qiu; Zhi-Ting Liu; Jia-Li Pang; Han-Biao Wu; Xu Liu; Ze-Min Yang; Xiong Li; Ji-Sheng Chen (Metabolic Brain Disease, 2021)

The downregulation of PpPG21 and PpPG22 influences peach fruit texture and softening - Ming Qian; Ze Xu; Zehua Zhang; Qin Li; Xiangyan Yan; Hangkong Liu; Mingyu Han; Furui Li; Jicheng Zheng; Dong Zhang; Caiping Zhao (Planta, 2021)

Variations in aeolian landform patterns in the Gonghe Basin over the last 30 years - Yu-han Qi; Mei-hui Pan; Ze-wen Hao; An-na Yang; Wen-xuan Xue (Journal of Mountain Science, 2021)

Paleoglacial and paleoclimate reconstructions during the global Last Glacial Maximum in the Longriba area, eastern Tibetan Plateau - Wei-lin Yang; Ye-song Han; Xu Peng; Ze-ze Ran; Qing Liu; Geng-nian Liu (Journal of Mountain Science, 2021)

Dynamic Variations in Brain Glycogen are Involved in Modulating Isoflurane Anesthesia in Mice - Ze Fan; Zhihao Zhang; Shiyi Zhao; Yuanyuan Zhu; Dong Guo; Bo Yang; Lixia Zhuo; Jiao Han; Rui Wang; Zongping Fang; Hailong Dong; Yan Li; et al. (Neuroscience Bulletin, 2020)
General anesthesia severely affects the metabolites in the brain. Glycogen, principally stored in astrocytes and providing the short-term delivery of substrates to neurons, has been implicated as an affected molecule. However, whether glycogen plays a pivotal role in modulating anesthesia–arousal remains unclear. Here, we demonstrated that isoflurane-anesthetized mice exhibited dynamic changes in the glycogen levels in various brain regions. Glycogen synthase (GS) and glycogen phosphorylase (GP), key enzymes of glycogen metabolism, showed increased activity after isoflurane exposure. Upon blocking glycogenolysis with 1,4-dideoxy-1,4-imino-D-arabinitol (DAB), a GP antagonist, we found a prolonged time of emergence from anesthesia and an enhanced δ frequency in the EEG (electroencephalogram). In addition, augmented expression of glycogenolysis genes in glycogen phosphorylase, brain (Pygb) knock-in (Pygb H11/H11 ) mice resulted in delayed induction of anesthesia, a shortened emergence time, and a lower ratio of EEG-δ. Our findings revealed a role of brain glycogen in regulating anesthesia–arousal, providing a potential target for modulating anesthesia.

SNP of AHSA2 gene in three cattle breeds using snapshot technology - Shu-Zhu Cheng; E. Guang-Xin; Cheng-Li Liu; Wang-Dui Basang; Yan-Bin Zhu; Ri-Su Na; Yan-Guo Han; Yan Zeng; Xiao Wang; Wei-Wei Ni; Bai-Gao Yang; Xing-Hai Duan; et al. (Journal of Genetics, 2020)

The effect of blastomere loss during frozen embryo transfer on the transcriptome of offspring’s umbilical cord blood - Yan-Ting Wu; Ze-Han Dong; Cheng Li; Dai-Zhan Zhou; Jun-Yu Zhang; Yan Wu; Jing-Jing Xu; Yu Wang; Xiao-Qun Ye; Jian-Zhong Sheng; Li Wang; He-Feng Huang (Molecular Biology Reports, 2020)

Orientin Improves Cognition by Enhancing Autophagosome Clearance in an Alzheimer’s Mouse Model - Yi Zhong; Qing-yu Zheng; Cheng-yan Sun; Ze Zhang; Kun Han; Ning Jia (Journal of Molecular Neuroscience, 2019)

The impact and mechanism of quaternary ammonium compounds on the transmission of antibiotic resistance genes - Yue Han; Zhen-Chao Zhou; Lin Zhu; Yuan-Yuan Wei; Wan-Qiu Feng; Lan Xu; Yang Liu; Ze-Jun Lin; Xin-Yi Shuai; Zhi-Jian Zhang; Hong Chen (Environmental Science and Pollution Research, 2019)

Potential hazards to a tunnel caused by adjacent reservoir impoundment - Bin Zhang; Han-xun Wang; Yi-wei Ye; Jun-liang Tao; Lian-ze Zhang; Lei Shi (Bulletin of Engineering Geology and the Environment, 2019)

Development and application of a simple recombinase polymerase amplification assay for rapid point-of-care detection of feline herpesvirus type 1 - Meng-zhi Liu; Xiao-hu Han; Long-quan Yao; Wen-kui Zhang; Bao-shan Liu; Ze-liang Chen (Archives of Virology, 2019)

An Optimized and Feasible Preparation Technique for the Industrial Production of Hydrogel Patches - Wei-Ze Li; Wen-Xia Han; Xu-Liang Hao; Ning Zhao; Xi-Feng Zhai; Li-Bin Yang; Shu-Miao He; Yu-Chuan Cheng; Han Zhang; Li-Na Fu; Yan Zhang; Ze Liang (AAPS PharmSciTech, 2018)

Long-term fertilization increases soil nutrient accumulations but decreases biological activity in navel orange orchards of subtropical China - Song-Ze Wan; Han-Jiao Gu; Qing-Pei Yang; Xiao-Fei Hu; Xiang-Min Fang; Anand Narain Singh; Fu-Sheng Chen (Journal of Soils and Sediments, 2017)

Salidroside accelerates fracture healing through cell-autonomous and non-autonomous effects on osteoblasts - Xiao Qin Guo; Lin Qi; Jing Yang; Yue Wang; Chuan Wang; Zong Min Li; Ling Li; Ye Qu; Dan Wang; Ze Min Han (Cell and Tissue Research, 2017)

A strategy for introducing an endangered plant Mosla hangchowensis to urban area based on nitrogen preference - Mei-Ying Fan; Kai-Xuan Pan; Wen-Juan Han; Yi-Jun Lu; Qi Shen; Meng Wang; Yuan Ren; Ze-Long Qu; Jie Chang; Ying Ge (Acta Physiologiae Plantarum, 2016)

Temporal variations of soil respiration at multiple timescales in a spruce-fir valley forest, northeastern China - Meng-Guang Han; Bao-Ku Shi; Guang-Ze Jin (Journal of Soils and Sediments, 2016)

Laboratory evaluation of Beauveria bassiana and Metarhizium anisopliae in the control of Haemaphysalis qinghaiensis in China - Qiaoyun Ren; Ze Chen; Jin Luo; Guangyuan Liu; Guiquan Guan; Zhijie Liu; Aihong Liu; Youquan Li; Qingli Niu; Junlong Liu; Jifei Yang; Xueqing Han; et al. (Experimental and Applied Acarology, 2016)

Thrombomodulin and High-Sensitive C-Reactive Protein Levels in Blood Correlate with the Development of Cerebral Infarction Among Asians - Yan Han; Shuai Wu; Qiang Hu; Jian-Qi Xiao; Dong-Mei Wei; Li-Li Liu; Ze-Zhi Li (Molecular Neurobiology, 2016)

RETRACTED ARTICLE: Effects of Common Polymorphisms in the MTHFR and ACE Genes on Diabetic Peripheral Neuropathy Progression: a Meta-Analysis - Shuai Wu; Yan Han; Qiang Hu; Xiao-Jie Zhang; Guang-Cheng Cui; Ze-Zhi Li; Yang-tai Guan (Molecular Neurobiology, 2015)

Isolation and Preliminary Functional Analysis of MxCS2: a Gene Encoding a Citrate Synthase in Malus xiaojinensis - De-Guo Han; Yan Shi; Bing Wang; Wei Liu; Ze-Yuan Yu; Bing-Yu Lv; Guo-Hui Yang (Plant Molecular Biology Reporter, 2015)

Does Haemaphysalis bispinosa (Acari: Ixodidae) really occur in China? - Ze Chen; Youquan Li; Qiaoyun Ren; Zhijie Liu; Jin Luo; Kai Li; Guiquan Guan; Jifei Yang; Xueqing Han; Guangyuan Liu; Jianxun Luo; Hong Yin (Experimental and Applied Acarology, 2015)

Susceptibility of the tick Haemaphysalis qinghaiensis to isolates of the fungus Metarhizium anisopliae in China - Qiaoyun Ren; Ming Sun; Guiquan Guan; Zhijie Liu; Ze Chen; Aihong Liu; Youquan Li; Miling Ma; Jifei Yang; Qingli Niu; Junlong Liu; Xueqing Han; et al. (Experimental and Applied Acarology, 2014)

Effect of copper-induced oxidative stress on sclerotial differentiation and antioxidant properties of Penicillium thomii PT95 strain - Ze-Qing Zhang; Wen-Jing Zhao; Dan-Dan Long; Lin-Ru Niu; Jian-Rong Han (World Journal of Microbiology and Biotechnology, 2014)

The role of Gracilaria lemaneiformis in eliminating the dissolved inorganic carbon released from calcification and respiration process of Chlamys farreri - Zeng Jie Jiang; Jian Guang Fang; Ting Ting Han; Yu Ze Mao; Jia Qi Li; Mei Rong Du (Journal of Applied Phycology, 2014)

Overexpression of a Malus xiaojinensis Nas1 Gene Influences Flower Development and Tolerance to Iron Stress in Transgenic Tobacco - De-Guo Han; Guo-Hui Yang; Ke-Dong Xu; Qin Shao; Ze-Yuan Yu; Bing Wang; Qiu-Lai Ge; Yang Yu (Plant Molecular Biology Reporter, 2013)

Aberrant upregulation of LRRC1 contributes to human hepatocellular carcinoma - Yandong Li; Bo Zhou; Jihong Dai; Ruifang Liu; Ze-Guang Han (Molecular Biology Reports, 2013)

SRPK1 contributes to malignancy of hepatocellular carcinoma through a possible mechanism involving PI3K/Akt - Bo Zhou; Yandong Li; Qing Deng; Haixiao Wang; Yuping Wang; Bing Cai; Ze-Guang Han (Molecular and Cellular Biochemistry, 2013)

Molecular characterization of LMW glutenin genes from Taeniatherum Nevski - Chang Han; Ze-Hong Yan; Shou-Fen Dai; Deng-Cai Liu; Yu-Ming Wei; You-Liang Zheng; Xiu-Jin Lan; Yuan-Ying Peng (Genetic Resources and Crop Evolution, 2011)

Expression of a novel gene FAM43B repressing cell proliferation is regulated by DNA methylation in hepatocellular carcinoma cell lines - Xiao Xu; Rui-Fang Liu; Bing-Bing Wan; Wen-Ming Xing; Jian Huang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2011)

The Mechanism of Liver Injury in Mice Caused by Lanthanoids - Min Fei; Na Li; Yuguan Ze; Jie Liu; Sisi Wang; Xiuaolan Gong; Yanmei Duan; Xiaoyang Zhao; Han Wang; Fashui Hong (Biological Trace Element Research, 2011)

Variation in the PTEN-induced putative kinase 1 gene associated with the increase risk of type 2 diabetes in northern Chinese - YANCHUN QU; LIANG SUN; ZE YANG; RUIFA HAN (Journal of Genetics, 2011)

RNA interference targeting CITRON can significantly inhibit the proliferation of hepatocellular carcinoma cells - Yinghui Fu; Jian Huang; Ke-Sheng Wang; Xin Zhang; Ze-Guang Han (Molecular Biology Reports, 2011)

Oxidative Stress in the Liver of Mice Caused by Intraperitoneal Injection with Lanthanoides - Min Fei; Na Li; Yuguan Ze; Jie Liu; Xiaolan Gong; Yanmei Duan; Xiaoyang Zhao; Han Wang; Fashui Hong (Biological Trace Element Research, 2011)

Liver-specific ZP domain-containing protein (LZP) as a new partner of Tamm-Horsfall protein harbors on renal tubules - Hai-Lian Shen; Zhi-Gang Xu; Li-Yu Huang; Dong Liu; Dao-Hong Lin; Jia-Bin Cao; Xin Zhang; Zhi-Qin Wang; Wen-Hui Wang; Peng-Yuan Yang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2009)

hBolA, novel non-classical secreted proteins, belonging to different BolA family with functional divergence - Yu-Bo Zhou; Jia-Bing Cao; Bing-Bing Wan; Xin-Rong Wang; Guo-Hui Ding; Hong Zhu; Hong-Meng Yang; Ke-Sheng Wang; Xin Zhang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2008)

EST-SSR DNA polymorphism in durum wheat (Triticum durum L.) collections - Han -Yan Wang; Yu -Ming Wei; Ze -Hong Yan; You -Liang Zheng (Journal of Applied Genetics, 2007)

ZBTB34, a novel human BTB/POZ zinc finger protein, is a potential transcriptional repressor - Jia Qi; Xin Zhang; Hai-Kuo Zhang; Hong-Meng Yang; Yu-Bo Zhou; Ze-Guang Han (Molecular and Cellular Biochemistry, 2006)

Hair concentrations of calcium, iron, and zinc in pregnant women and effects of supplementation - Po Lau Leung; Han Ming Huang; Da Ze Sun; MeI Guang Zhu (Biological Trace Element Research, 1999)

Hair and serum calcium, iron, copper, and zinc levels during normal pregnancy at three trimesters - Han Ming Huang; Po Lau Leung; Da Ze Sun; Mei Guang Zhu (Biological Trace Element Research, 1999)